(untitled) (Web of Teachers: Inderscience Research, 2025)
This article comprehensively analyzes the role of artificial intelligence (AI) technologies in society, their positive and negative aspects. In recent years, artificial intelligence has been deeply penetrating almost all areas of science, technology, economics, education, medicine, and everyday life. This technology, which imitates human intelligence, has great potential, but also poses certain risks and problems. The article emphasizes the positive aspects of artificial intelligence, including increasing work efficiency, quickly and accurately solving complex problems, and reducing errors due to the human factor. In particular, AI plays an important role in the early detection of diseases, improving diagnostic and treatment processes in the medical field. In education, the possibilities of individualizing the learning process, developing distance learning, and quickly analyzing knowledge are expanding. Also, saving time and resources through automation in production and industry, and increasing economic efficiency are among the important advantages of artificial intelligence.